Sphingosine-1-phosphate analogue FTY720 exhibits a potent anti-proliferative effect on glioblastoma cells - Kolodziej, Malgorzata A.; Al Barim, B.; Nagl, J.; Weigand, Markus A.; Uhl, E.; Uhle, Florian; Di Fazio, P.; Schwarm, F. P.; Stein, M. (International journal of oncology, 2020)
Sphingosine-1-phosphate (S1P) plays a key role in cell survival, growth, migration, and in angiogenesis. In glioma, it triggers the activity of the S1P-receptor 1 and of the sphingosine kinase 1; thus influencing the survival rate of patients. The aim of the present study was to investigate the anti-proliferative effect of the S1P analogue FTY720 (fingolimod) in glioblastoma (GBM) cells. A172, G28, and U87 cells were incubated with micromolar concentrations of FTY720 or temozolomide (TMZ) for 24 to 72 h. Proliferation and half maximal inhibitory concentration (IC50) were determined by using the xCELLigence system. FACS analysis was performed to check the cell cycle distribution of the cells after a 72-h incubation with FTY720. This was then compared to TMZ-incubated and to untreated cells. Gene expression was detected by RT-qPCR in A172, G28, U87 and three primary GBM-derived cell lines. FTY720 was able to reduce the number of viable cells. The IC50 value was 4.6 mu M in A172 cells, 17.3 mu M in G28 cells, and 25.2 mu M in U87 cells. FTY720 caused a significant arrest of the cell cycle in all cells and stabilized or over-expressed the level of AKT1, MAPK1, PKCE, RAC1, and ROCK1 transcripts. The TP53 transcript level remained stable or was downregulated after treatment with FTY720. FTY720 may be a promising target drug for the treatment of GBM, as it has a strong anti-proliferative effect on GBM cells.